AN ANALYSIS OF SPEECH FUNCTION ON THE CIGARETTES ADVERTISEMENT - Nova Andriani (Journal MELT (Medium for English Language Teaching), 2018)
This research deals with speech function on the cigarettes advertisement. The objective of this study is to find out the types of speech function and the most dominant types of speech function on the cigarettes advertisement. Descriptive qualitative method was carried out to analyze the data. Source of data of this research would be taken from cigarettes advertisement. Of the selected from table, table 1 – table 7. In collecting the data, some references related to speech function found out in the library. In analyzing the data, first each slogan in each cigarettes advertisement, second to identify the types of speech function which are mostly dominant, and the last to find the dominant type of speech function. The cigarettes advertisement were analyzed on the occurrences of speech function based on the types of speech function on the cigarettes advertisement. There were 118 items, namely statements 74 items (62,7%), questions 14 items (11,8%), offer 13 items (11,1%), and command 17 items (14,4%). And the dominant speech function is statements 118 items (62,7%).